AB070. The risk factors for intravesical recurrence after upper-tract urothelial carcinoma surgery - Zeng, Shuxiong (Transl Androl Urol, 2018)
BACKGROUND: Objective to explore risk factors for intravesical recurrence (IVR) after surgical treatment of upper-tract urothelial carcinoma (UTUC). METHODS: A total of 445 patients with complete follow-up data and underwent UTUC surgery in our hospital from January 2008 to December 2017 were collected. Baseline demographics, surgical treatment method, postoperative pathology, follow-up data and other related information were collected. Risk factors of the IVR were analyzed by univariate and multivariate Cox proportional hazard regression model. RESULTS: The average follow-up time was 33.5 months, and the IVR was 18% (80/445), of which 66.3% (53/80) IVR occurred within 1 year after surgery. Univariate Cox analysis revealed that patients older than 65 years old, with history of bladder cancer, nephron-sparing measures (endoscopic ablation or segmental ureterectomy), and lower part of ureteral cancer were closely related to IVR after UTUC (P>0.01). These risk factors were also found to be an independent risk factor for IVR in the multivariate Cox analysis. CONCLUSIONS: Patients of 65 years older, with history of bladder cancer, nephron sparing surgery and lower part of ureteral cancer were independent risk factors for IVR after UTUC. UTUC patients with these risk factors should have carefully surveillance and have cystoscopy examination regularly.